Pengaruh Kombinasi Aplikasi Insektisida dan Varietas Unggul terhadap Intensitas Serangan Kutu Kebul dan Hasil Kedelai - Inayati, Alfi; Marwoto, Marwoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The whitefly, B. tabaci Gennadius, is an important soybean pest causing yield losses up to 100%. No effective method was available to control this pest. Integrated control methods using combinations of insecticide and tolerant soybean varieties are expected to give good results on controlling the whitefly. An experiment was carried out, arranged in a split plot design with two factors and three replications during the dry season (DS) I and DS II of 2010 at Muneng Experimental Farm, Probolinggo, East Java. The main plots were the insecticide applications and the sub plots were 6 soybean varieties. Results of the experiment showed that application of 2 ml/l profenofos 500 g/l at 14 and 21 days after planting (DAP) followed with combination of 1 ml/l lamdasihalotrin 106 g/l and tiamektosam 141 g/l at 28, 35 and 42 DAP reduced whitefly population by 50%. The use of insecticides to control pest also reduced soybean yield losses up to 81% in DS I and 29% in DS II. Soybean variety Anjasmoro was very susceptible to the pest and was not recommended to be grown in the whitefly endemic area. The use of tolerant varieties such as Gepak Kuning, Gepak Ijo, Kaba, Wilis, and Argomulyo produced yields of about 1.52 t/ha. The combination of insecticides application and tolerant varieties reduced soybean yield losses up to 58%.